In Search of Perfect Harmony: Tartini's Music and Music Theory in Local and European Contexts - Sukljan, Nejc (2023)
Giuseppe Tartini (1692-1770) made history both as an outstanding composer and as an exceptional music theorist. Especially after he began to devote himself to speculative reflections of music, Tartini seems to have been searching for harmony between music theory (which he studied in depth, even reaching back to ancient concepts of music) and musical practice (his daily routine as composer and violinist at St Anthony's Basilica in Padua and as violin teacher). The present 2nd volume of the series focuses on both Tartini's musical language and his theoretical deliberations.